Phylogenetic and population structural inference from genomic ancestry maintained in present‐day common wheat Chinese landraces. (27th June 2019) - Wu, Xiyan; Ding, Baoxu; Zhang, Bingqi; Feng, Jiaojiao; Wang, Yibing; Ning, Chao; Wu, Haidan; Zhang, Fan; Zhang, Qun; Li, Ning; Zhang, Zhibin; Sun, Xuhan; et al.
Summary: Hexaploid common wheat is one of the most important food crops worldwide. Common wheat domestication began in the Fertile Crescent of the Near East approximately 10 000 years ago and then spread west into Europe and eastward into East Asia and China. However, the possible spreading route into and within China is still unclear. In this study, we successfully extracted DNA from single ancient wheat seeds and sequenced the whole genome of seven ancient samples from Xiaohe and Gumugou cemeteries in Xinjiang, China. Genomic inference and morphological observation confirmed their identity as hexaploid common wheat grown in prehistoric China at least 3200 years before present (BP). Phylogenetic and admixture analyses with RNA‐seq data of modern hexaploid wheat cultivars from both China and Western countries demonstrated a close kinship of the ancient wheat to extant common wheat landraces in southwestern China. The highly similar allelic frequencies in modern landraces of the Qinghai‐Tibetan plateau with the ancient wheat support the previously suggested southwestern spreading route into highland China. A subsequent dispersal route from the Qinghai‐Tibetan plateau margins to the Yangtze valley was proposed in this study. Furthermore, the common wheat populations grown in the Middle and Lower Yangtze valley wheat zones were also proposed to be established by population admixture with the wheat grown in the Upper Yangtze valley. Our study reports ancient common wheat sequences at a genome‐wide scale, providing important information on the origin, dispersal, and genetic improvement under cultivation of present‐day wheat landraces grown in China. Significance Statement: The whole‐genomic sequencing of DNA extracted from single ancient seed provides an improved technical strategy in archaeological plant research field. In addition, our results have provided important information on the origin, dispersal, and genetic improvement under cultivation of present‐day wheat landraces grown in China.